HIKIJI, Rose Satiko Gitirana. 2006. A Música e o Risco. São Paulo: Edusp. - Montardo, Deise Lucy Oliveira (Campos - Revista de Antropologia, 2007)
Resenha do livro A Música e o Risco, de Rose Satiko Gitirana Hikiji, publicado em 2006.